Pengaruh Media Papan Perkalian Terhadap Hasil Belajar Matematika Siswa Kelas III SD YPK Elim Kota Sorong - Novela Baru; Ahmad Yulianto; Anis Alfian Fitriani (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2024)
The purpose of this study was to determine the Influence of Multiplication Board Media on Mathematics Learning Outcomes of Grade III Students of SD YPK Elim Sorong City. This type of research uses Quantitative Research with the research design used is a pre-experimental design  with the type One-Group Pretest-posttest. The population is class III A students with a total of 19 students with a sampling technique carried out by nonprobability sampling, namely purporsive sampling. The instruments used are observation sheets and essay tests to measure student learning outcomes, while the results of the analysis of student learning completeness on the average posttest score are 83.84. The reliability test results obtained by Cronbachs Alpha for student responses amounted to 0.852 which means it has a high level of reliability with the normality test of student posttest learning outcomes  having a significance level of 0.028 > 0.05. The hypothesis test  obtained tcount of 7.001 with df = n – 1 (19-1=18) obtained ttable of 1.729. Based on the results of the analysis of value data, namely tcalculate > ttable (-7.001> 1.729), with a magnitude of significance level of 0.05, the hypothesis is accepted. Thus, it can be concluded that there is an influence of Multiplication Board Media on the Mathematics Learning Outcomes of Grade III Students of SD YPK Elim Malanu in Sorong City.